Numerical and experimental analysis of moisture transfer for convective drying of some products - Öztop, Hakan Fehmi; Akpinar, Ebru Kavak (Pergamon-Elsevier Science Ltd, 2008)
Numerical and experimental results of moisture transfer in drying process for apple and potato slices are compared in this study. Experimental results are obtained using a cyclone type dryer. Two-dimensional analysis of beat and moisture transfer during drying of objects is carried out solving heat and mass equations using finite-volume approach. Thus, moisture distributions inside the moist objects are obtained at different time steps. Comparison of results showed that there is a considerably high agreement between experimentally measured data and predicted values. Moist distribution also presented inside the products at different time periods. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: drying; numeric; mass transfer; cyclone dryer; finite-volume method